The More Doctors Program and the Curricular Guidelines for Medical courses: a comparative analysis among higher education institutions - Annabelle de Fátima Modesto Vargas; Diogo de Souza Vargas; Mauro Macedo Campos; Rodrigo da Costa Caetano (Faculdade de Medicina de Botucatu (Unesp), 2019)
Abstract The article was constructed from an exploratory, documentary research and investigates the curricular matrices of the medicine courses of three higher education institutions, trying to identify the weight they give to a more humanistic education of their students, in accordance with what is recommended by the More Doctors Program (PMM). Two Brazilian institutions were examined, one public and one private, both in Rio de Janeiro, and also a third institution, located in Cuba. In the education of Cuban doctors, importance is given to disciplines categorized as "Public Health Education". Contrary to this design, the education of Brazilian doctors reflects the conflict between teaching and the reality of the country, visible in the difficulty in educating doctors to work in primary care and in retaining them in the most remote places of Brazil.